2022
DOI: 10.1007/s11606-021-07361-9
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Homebound Older Adults During the COVID-19 Pandemic

Abstract: BACKGROUND: Homebound older adults have heightened risks for isolation and negative health consequences, but it is unclear how COVID-19 has impacted them. We examine social contact and mood symptoms among previously homebound older adults during the COVID-19 pandemic. DESIGN/SETTING: Cross-sectional analysis using data from the National Health and Aging Trends Study (NHATS), a nationally-representative longitudinal study of aging in the USA. PARTICIPANTS: A total of 3,112 community-dwelling older adults in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…While the risk can be lowered with vaccination, being homebound frequently limits access to this potentially life-saving intervention ( Dar et al, 2021 ). During the global public health emergency, barriers to vaccine access for this vulnerable group have included increased social isolation, loneliness, anxiety, and depression ( Ankuda et al, 2022 ; Sørbye et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the risk can be lowered with vaccination, being homebound frequently limits access to this potentially life-saving intervention ( Dar et al, 2021 ). During the global public health emergency, barriers to vaccine access for this vulnerable group have included increased social isolation, loneliness, anxiety, and depression ( Ankuda et al, 2022 ; Sørbye et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies shown the majority of older adults are mostly dependent on their friends and family for various reasons and they are often in touch with them in person or virtually by phone call, text, e-mail, or video chat. However, with the advent of Covid-19, people spend less time interacting with older people (Freedman, Hu, & Kasper, 2021; Ankuda, Kotwal, Reckrey, Harrison, & Ornstein, 2022). Given that older adults were restricted to engage in social activities, strictly advised to maintain health compliances, and experienced limited physical social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…People were discouraged from engaging in in-person communication and instead encouraged to adopt virtual interactions through phone calls, text or e-mail messages, and video-calling. Research also shows that homebound older adults felt limited social contact due to Covid-19 (Ankuda et al, 2022). It also reported that older people were mostly contacted through email, text, and social media during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first wave of the coronavirus disease 2019 (COVID‐19) pandemic brought sweeping changes to the lives of older adults. In the United States, high risk of severe COVID‐19 led many older adults to adopt behaviors to limit its spread, including staying at home; 1 reducing social contact with non‐resident family and friends; 2 and adopting related behavioral changes such as hand washing, masking, and physical distancing. 3 , 4 Other studies suggest increased reports of psychosocial distress among older adults during this time, 5 , 6 , 7 as well as declines in physical activity.…”
Section: Introductionmentioning
confidence: 99%